In-flight wingtip folding: inspiration from the XB-70 Valkyrie - Dussart, Gaétan; Lone, Mudassir; O'Rourke, Ciaran; Wilson, Thomas (Embry-Riddle Aeronautical University, 2019)
Wingip folding can be used to extend aircraft wingspan, allowing designers to take advantage of reduced induced drag whilst respecting ground operational limitations. Such devices can also be used in-flight for a variety of other benefits including load alleviation and flight control. The majority of in-flight folding research takes inspiration in past developments made on the XB-70 Valkyrie, which used the folding devices for stability and lift performance benefits. In this paper, the authors investigate the capabilities of the folding wingtip system and potential scaling to large civil aircraft. Manufacturing details are used to size the actuators whilst the aerodynamic loading acting on the wingtip hinges is found from flight test results. Dimensions and aerodynamic loading at cruise of a set of conventional civil aircraft wing are used to evaluate the scaling potential of the system for controlled in-flight folding. An estimate of the weight penalty due to the folding device is also given and compared to structural weight savings on the XB-70. The results presented herein help in the evaluation of conventional actuator limits for in-flight folding using arguably the most inspiring military example of wingtip folding so far.